Integration indigenous science in merdeka curriculum to strengthen scientific literacy and environmental care in elementary schools: Need analysis - Prasetyo, Zuhdan Kun; Syawaludin, Ahmad; Desstya, Anatri (Edelweiss Applied Science and Technology, 2024)
This research aims to analyze the needs of integration indigenous science approach in the Merdeka Curriculum to strengthen scientific literacy and environmental care in elementary schools for elementary school students. This research uses a qualitative approach with a case study design. The subjects of this study were 160 elementary school teachers in one of the big cities in Indonesia. Research data collection techniques consist of interviews and questionnaires. The research data analysis technique used an interactive model consisting of data condensation, data presentation, and drawing conclusions. The results of this research show that the teachers propose the reconstruction of indigenous science into scientific science and its integration in learning based on the national curriculum. Analysis of the needs for multimodal reconstruction of indigenous science in science learning in elementary schools shows a very important category. Multimodal indigenous science is proposed from Javanese culture which is specified with the needs of the elementary school sciences scope with the integration of indigenous science carried out in the content, process and product aspects. The results of the initial study recommend that teachers and future researchers can develop learning tools with a multimodal indigenous science approach in the Merdeka Curriculum to strengthen scientific literacy and care for the environment in elementary schools.